Legal Co-Creation of Public Authorities and Civil Society as Trajectory of Russian Law-Making System - Vasily V. Trofimov (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
The current development of Russian state, society, and law is dynamic but ambiguous. The author studied the Russian law-making system through the prism of legal co-creation between official public authorities and civil society that join forces to create laws that meet the interests of both the state and the society. Legal co-creation is an essential resource for optimizing and improving the law-making system. General scientific and special scientific methods made it possible to establish the importance of legal co-creation of the authorities and the population as part of the domestic law-making system with its theoretical constructs and practical benefits. A constructive dialogue between the government and the society in the law-making sphere produces co-creative law-making decisions. This opinion is supported by domestic jurists and politicians. In addition to the general theoretical analysis of the phenomenon of legal co-creation, the author selected opinions of like-minded foreign researchers. Mechanisms of legal co-creation in the law-making system have good prospects and need to be developed.